Konsep desain taman yoga di Balitrees Retreats, Desa Sesandan, Kabupaten Tabanan - Sintya, Ni Komang; Semarajaya, Cokorda Gede Alit; Astawa, I Nyoman Gede (Jurnal Arsitektur Lansekap, 2022)
Sesandan Village is a tourism village that offers yoga activities as one of its tourist attractions. Yoga activities are often carried out in a semi-open space without pay attention to the outside area or the environment, such as at the Balitrees Retreats yoga venue. Even though the environment with beautiful nature can help provide peace and tranquility. This research aims to produce a garden design concept that can support yoga activities at Balitrees Retreats. The healing garden used as a reference in this design concept because it has a purpose for yoga. The research method used is a survey method with data collection techniques through observation, interviews, and literature. The stages of the research carried out include inventory, analysis, synthesis, and concepts plan. Creating a design concept based on the needs of the implementation of yoga by paying attention to natural elements (softscape) and artificial elements (hardscape). The design concept produced in this research is Padma Mandala. This design concept contains the value of silence to aid in the centering of the mind which is the essence of yoga practice. This is expected to maximize the implementation of yoga and accelerate the physical and psychological healing process of its users.